Religious Workers' Density and the Racial Earnings Gap - Lozano, Fernando; Cheng, Jessica Shiwen (American Economic Review, 2016)
We explore differences between Black and White Non-Hispanic workers in the relationship between childhood exposure to religious workers and a worker's labor market outcomes thirty years later. We identify this relationship by exploiting two sources of variation: we use changes in the number of religious workers within states, and we use states' differences by following workers who moved to a different state. Our results suggest that a one percent increase in the number of clergy increases the earnings of Black workers by a range from 0.027 to 0.082 percent relative to the increase in the earnings of White workers.